THE CORRELATION BETWEEN GRAMMAR COMPETENCY AND SPEAKING ABILITY OF THE EIGHTH GRADE STUDENTS IN SMPN 1 PALU - aldi saputra; Nurasmawati; Yuni Amelia (Datokarama English Education Journal, 2021)
This research was motivated by the problems experienced by some of the eighth grade students in SMPN 1 Palu. The students still had some difficulties when expressing their ideas or feelings by using English. They had various reasons for this. Most of them said that grammar is one of the causes of their difficulties in speaking English. This research was a correlational design, the technique of collecting data using test. There were two kinds of test such as written test and oral test as the research instrument. The written test was used to measure students’ grammar competency and oral test was used to measure students’ speaking ability. The researcher used Pearson Product Moment Correlation in analyzing the data by using SPSS program 26 version. Based on the results of the correlation analysis between the students’ grammar competency and the students speaking ability, the r value was obtained at 0.407 (r > 0.361) with p = 0.023 (p <0.05) indicating that there was a significant positive correlation between students’ grammar competency and students’ speaking ability. This supported the alternative hypothesis to be accepted and the null hypothesis to be rejected. It could be concluded that there was a correlation between grammar competency and speaking ability at the eighth grade students of SMPN 1 Palu in the academic year of 2020/2021.